2018
DOI: 10.1177/0825859717750522
|View full text |Cite
|
Sign up to set email alerts
|

Feelings of Burden in Palliative Care

Abstract: Findings in the palliative care patients' medical records are inasmuch important, as they point at the health-care staff's awareness of possible weights and tasks that might be burdensome for patients and their families. Attention should be drawn to the documentation of medical records in order to identify recurrent difficulties and to help discuss these.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…As examined above, content analysis is used in several fields due to its advantages of embracing both qualitative and quantitative aspects and processing comprehensive data [ 62 , 70 ]. In recognition of its research potential, the public health field is also increasingly using content analysis research, as exemplified by suicide-related social media content analysis [ 71 ], an analysis of children’s books in association with breast cancer [ 72 ], and an analysis of patients’ medical records [ 73 ].…”
Section: In-depth Review Of Qualitative Research Methodsmentioning
confidence: 99%
“…As examined above, content analysis is used in several fields due to its advantages of embracing both qualitative and quantitative aspects and processing comprehensive data [ 62 , 70 ]. In recognition of its research potential, the public health field is also increasingly using content analysis research, as exemplified by suicide-related social media content analysis [ 71 ], an analysis of children’s books in association with breast cancer [ 72 ], and an analysis of patients’ medical records [ 73 ].…”
Section: In-depth Review Of Qualitative Research Methodsmentioning
confidence: 99%
“…SPB also can affect patients' quality of life (QOL), treatment decisions, and desire of survive. 10 , 17 , 19 In conjunction with the above, SPB in this review was defined as a negative experience arising from an individual's illness and care needs affecting others, which can lead to adverse physical and psychological effects on the patient themselves and have impacts on subsequent treatment decisions. Some studies have shown that interventions aimed at patients' physical and psychological problems can improve SPB to a certain extent.…”
Section: Introductionmentioning
confidence: 99%
“…For cancer patients, they experience concerns about burdening their caregivers, leading to negative psychological feelings known as self-perceived burden (SPB; Rakic et al, 2018 ). SPB has been cited as ‘empathetic attentiveness arising from the imbalance of an individual’s disease and caring needs on others, causing guilt, distress, and loss of self-awareness’ ( Cousineau et al, 2003 ; McPherson et al, 2007b ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been noted that 19–65% of patients with advanced cancer undergo moderate to extreme SPB ( Cousineau et al, 2003 ; Chochinov et al, 2007 ; McPherson et al, 2007a ). SPB can also cloud the relationship between patients and their caregivers, placing a number of negative effects on them ( Rakic et al, 2018 ; Chen et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%